2013
DOI: 10.1515/jbcpp-2013-0001
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate at therapeutic concentration alters glucose metabolism and induces regulatory T-cell differentiation in alloreactive human lymphocytes

Abstract: DCA inhibits aerobic glycolysis and induces Treg differentiation in human alloreactive lymphocytes. This could result in decreased immunosurveillance in case of its use as an anticancer drug. However, DCA could play a role as an immunosuppressant in the fields of transplantation and autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…Mechanisms that control cell metabolism to support the specific functional needs of these cells have been described only recently (MacIver et al, 2013), but have proven promising (Bian et al, 2009; Eleftheriadis et al, 2013; Ostroukhova et al, 2012; Shi et al, 2011). To date, pharmacologic approaches have provided limited mechanistic insight, and the role of glucose uptake has been uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms that control cell metabolism to support the specific functional needs of these cells have been described only recently (MacIver et al, 2013), but have proven promising (Bian et al, 2009; Eleftheriadis et al, 2013; Ostroukhova et al, 2012; Shi et al, 2011). To date, pharmacologic approaches have provided limited mechanistic insight, and the role of glucose uptake has been uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…DCA has also been shown to reduce proinflammatory cytokine production and promote FoxP3 expression in vitro and in several in vivo inflammatory models (19)(20)(21), although the mechanisms involved have not been established.…”
Section: T Cells Undergo Metabolic Reprogramming Toward a Glycolytic mentioning
confidence: 99%
“…While DCA has been previously shown to suppress inflammation in arthritis, asthma, and alloreactivity (19)(20)(21), the specific effect on the differentiated CD4 + T cell subsets has not been examined in vivo. We therefore tested the ability of DCA to suppress the Th17-mediated inflammatory diseases.…”
Section: Inhibition Of Pdhk In Vivo Differentially Affects Th17 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using multiple pharmacological inhibitors and activators, it was shown that differential metabolic programs could regulate Treg cell lineage differentiation both in vivo and in vitro (25, 37, 38). Specifically, inhibition of glycolysis with the glucose analogue 2-deoxyglucose (2-DG) - a prototypical inhibitor of the glycolytic pathway - promoted induction of mouse Treg cells in vitro, in the presence of polarizing cytokines such as transforming growth factor (TGF)-β and IL-2 (5, 25).…”
Section: Effects Of Metabolism On Foxp3 Expressionmentioning
confidence: 99%